2020
DOI: 10.3390/ph13120465
|View full text |Cite
|
Sign up to set email alerts
|

Novel Isoniazid-Carborane Hybrids Active In Vitro against Mycobacterium tuberculosis

Abstract: Tuberculosis (TB) is a severe infectious disease with high mortality and morbidity. The emergence of drug-resistant TB has increased the challenge to eliminate this disease. Isoniazid (INH) remains the key and effective component in the therapeutic regimen recommended by World Health Organization (WHO). A series of isoniazid-carborane derivatives containing 1,2-dicarba-closo-dodecaborane, 1,7-dicarba-closo-dodecaborane, 1,12-dicarba-closo-dodecaborane, or 7,8-dicarba-nido-undecaborate anion were synthesized fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…The donor-acceptor distance is 3.16 Å, indicating a relatively strong bond for a carbon atom acting as a donor. This is another confirmation that the carborane groups can participate in weak H-bonding interactions [9,19], and the acidic nature of the C-H group was previously observed for free carboranes [33].…”
Section: X-ray Structural Analysissupporting
confidence: 83%
See 2 more Smart Citations
“…The donor-acceptor distance is 3.16 Å, indicating a relatively strong bond for a carbon atom acting as a donor. This is another confirmation that the carborane groups can participate in weak H-bonding interactions [9,19], and the acidic nature of the C-H group was previously observed for free carboranes [33].…”
Section: X-ray Structural Analysissupporting
confidence: 83%
“…Progressive addition of ct-DNA at the concentration of 1.25-15 µM to a fixed amount of modified naphthalic anhydride or naphthalimide (10 µM concentration) decreased absorbance for almost all the tested modified conjugates, except conjugates 14, 15, and 22-27 for which changes in absorbance were not observed. For all other conjugates, the absorption spectra demonstrated no bathochromic effect (6-10, 16, 18, 36-43, 54, 56, 58, 60, and 61) or slight bathochromic shifts (11,17,19, 55, and 59) (1-2 nm). It should be noted that mitonafide also caused a small bathochromic shift, which was confirmed in our study [9] and the literature [41].…”
Section: Uv-vis Spectra Measurementmentioning
confidence: 91%
See 1 more Smart Citation
“…A number of isoniazid derivatives of carborane containing 1,2-dicarba- closo -dodecaborane, 1,7-dicarba- closo -dodecaborane, 1,12-dicarba- closo -dodecaborane, or 7,8-dicarba- nido -undecaborate anion were synthesized [ 72 ]. The compounds were tested in vitro against the Mycobacterium tuberculosis (Mtb) H37Rv strain and its mutant (ΔkatG), deficient in catalase-peroxidase synthesis (KatG).…”
Section: Adamantane-type Derivatives With Anti-viral Activitymentioning
confidence: 99%
“…It was observed that in recent years, isoniazid and its derivatives have received attention and are being widely studied. The derivatives of isoniazid are evaluated for their various biological activities, such as anti-inflammatory [8], anticancer [9,10], antimicrobial [11][12][13], anti-tubercular [2,11,[14][15][16][17], and in the treatment of Alzheimer's disease [18].…”
Section: Introductionmentioning
confidence: 99%